TRILOBITES AND SEDIMENTARY SETTINGS FROM THE LOWER ORDOVICIAN (TREMADOCIAN; BIENVILLIA TETRAGONALIS BIOZONE) OF ITURBE, JUJUY PROVINCE, ARGENTINA (Ameghiniana, 2020)
In the Argentinian Cordillera Oriental, the Iturbe River area represents an intermediate territory between Sierra de Santa Victoria to the north and the Quebrada de Humahuaca to the south. Lower Ordovician outcrops of this region were cited in the literature as highly fossiliferous, although they are still imperfectly known. A Tremadocian succession of the Santa Rosita Formation near the village of Iturbe, Jujuy Province, is described herein. It displays different marine paleoenvironments and a relatively high-diversity trilobite assemblage. The sedimentary features of the lower and middle parts of the succession denote deposition in upper offshore and offshore transition environments, whereas those of the upper part are characteristic of a deeper, lower offshore setting. Taxa recognized include Gymnagnostus sp., Micragnostus iturbensis sp. nov., Geragnostus callaveiformis Harrington and Leanza, Geragnostus sp., Conophrys cf. salopiensis (Callaway), Leptoplastides granulosus (Harrington), Bienvillia tetragonalis (Harrington), B. rectifrons (Harrington), Parabolinella boliviana Juarez Huarachi, Asaphellus stenorhachis (Harrington), Apatokephalus tibicen Pribyl and Vanek, and Pyrimetopus sp. This association indicates correspondence with the Bienvillia tetragonalis Zone (lower upper Tremadocian); a unit that to date is recorded with confidence only in a few localities of the Cordillera Oriental, in diverse facies. This study provides information on the morphology of several key taxa of the biozone, as well as new evidence in favour of a correlation with the Conophrys salopiensis Zone of England. The assemblage studied is assignable to the middle Tremadocian Olenid-Asaphellus biofacies, which occurs typically in upper offshore to offshore transition deposits.